A magyar regionális politika súlypontjai - Horváth, Gyula (Tér és Társadalom, 1992)
The paper summarizes the possible new features of Hungarian regional policy on the basis of an investigation prepared by the Regional Research Center of the Hungarian Academy of Sciences for the authorization of the Ministry of Environment in 1991 in order to support the preparatory works of the law on regional development. The fundamental reason of the failures of previous regional policy, which can still be sensed in some spheres, was the lack of a mutual relationship between the economic and regional policies. The institutional-organizational network and the operational organizations of regional policy were separated. Regional policy had, in the first place, some sort of social-policy aims, and financial restrictions significantly limited the means, and at the same time, the scope of activity of regional policy. From the pont of view of solving the tasks of Hungarian economic modernization efficiently, the researchers participating in the project unanimously voted for the innovation-oriented model from among the possible regional development methods. This sub-branch of regional policy is the most likely to support the mobilization of local resources, the restructuring of the economy, and the creation of the system of economic incentives. The proposed, especially important, aim of new regional policy should be the moderation of regional differences, and the creation of a situation where the backward, depressed regions can join up with the rest. The wording of this objective is well founded by the following requirements: social policy implications, the need to increase economic productivity, and general political implications. The study devotes special attention to the consequeces of restructuring the infrasturcture, and indicates that the new projects on the development of infrastructure should primarily concentrate on the development of technical and intellectual infrastructure serving the creation of a modern economic structure, and not so much the improvement of living standards in the region. In order to modernize the structures, the strategy of Hungarian regional development, especially in the phase of transformation into a market economy, has to put special emphasis on industrial development, though it is different from the models of developed market economies. However, it has to be done in close correlation with the creation of an economic environment which is capable of and ready for re-industrialization. The fundamental trend of future development in Hungarian regional policy is the formation and creation of the means and the institutional-organizational elements (development of the local organizational and promotional network of regional development, the widening of the number of actors in regional development with the agents of financing, social aspects and the representation of interests) and the creation of the system of financial support (regional development incentives, subsidies, etc.). Finally, the paper investigates the relationship between the administrative system and regional policy. The study points out that the means and the institutional network of regional policy have to be developed on the basis of the partnership of central government and the local authorities. While previous Hungarian administration followed the logic of bureaucracy, the new democratic management, with more than 3000 decision-makers, was put into the state cf disintegration. The future of the structure of Hungarian regional management is uncertain. The reasearchers carrying out the investigation are positive that regional policy meeting the Buropean norms requires a sub-national level with wide scope of research fields in Hungary ais well. However, not only the actual counties have to be modernized for this purpose, but ailso a new regional-administrative system has to be developed in the long run.